Incongruency in the Response Priming Paradigm Influences Speech Muscle Activity. - Kriegel, Zoe; Fullenkamp, Adam M.; Whitfield, Jason A. (Journal of Speech, Language & Hearing Research, 2025)
Purpose: The current investigation examined the effects of a verbal response priming paradigm on lip and jaw kinematics and facial muscle activity before and during verbal responses. Method: Thirty younger adult control participants completed two verbal naming tasks, choice response and response priming, while acoustic, optical kinematic, and perioral electromyographic data were collected. The response priming task required a quick and accurate verbal response for congruent and incongruent trials. For both tasks, the response set was limited to three color words--red, green, and black--to permit comparison across tasks. Results: Facial muscle activity before the spoken response was greater for incongruent response priming trials compared to the choice or congruent response priming trials. Incongruent prime-target pairs in the response priming paradigm resulted in expected longer verbal response times compared to their congruent counterparts. However, lip and jaw kinematic range of motion and spatial variability were consistent across tasks and conditions. Individual-level data revealed variability in participant responses to experimental conditions that may present a range of expected responses for healthy control populations. Conclusions: These findings suggest that, in addition to more central effects, some peripheral aspects of speech motor control may be modified by cognitive-linguistic conflict. Future research may investigate the ways in which these effects may differ for individuals with motor speech disorders that affect the selection and implementation of desired speech motor programs.